THE ROLE OF INNOVATION IN IMPLEMENTING CONCENTRATION STRATEGIES: ANALYSIS IN TECHNOLOGY - BASED CREATIVE INDUSTRY - Bayu Dwi Rahmanto (Journal of Entrepreneurship and Financial Technology, 2023)
This study is to describe the role of innovation strategy in efforts to improve business performance and competitive advantage in technology-based creative industries. This research is expected to provide an overview of the condition of the innovation strategy among creative industry players, especially in the field of digital business. This study uses a descriptive qualitative approach to investigate technology-based creative industry entrepreneurs. Retrieval of respondents or informants using the snowball technique. Data were obtained by conducting in-depth interviews, observation and documentation studies. After the data is obtained in the field, then the data will be checked for validity using the data source triangulation technique. The next step, qualitative data was analyzed in three stages, namely data reduction, data presentation and conclusion. The results of the study show that technology-based creative entrepreneurs are quite open to new ideas and ideas in developing the company's business and have made aspects of innovation a part of their business strategy. However, only a small number of respondents made investments to develop their business enterprises.